Technology diffusion: Application of slicer machine in making milkfish crackers in Kampung Tambak Asri, Surabaya - Izza Anshory; Indah Sulistiyowati; Lukman Hudi (Universitas Muhammadiyah Magelang, 2023)
Members of the At-Taubah Assembly of Aisyiah Branch Leadership (PCA) Krembangan, located in Tambak Asri Village Surabaya, have difficulties in processing milkfish into fish crackers. The purpose of this community service is to provide knowledge on how to process milkfish into crackers using slicer machine tools. The method used in this activity consisted of three stages, namely socialization, demonstrating the processing of milkfish crackers, and giving a cracker cutting machine. The results of this community service are the members of Majelis Ta'lim At-Taubah become aware and understand how to use a slicer machine for the process of making milkfish crackers.